DETERMINATION OF ANTIOXIDANT ACTIVITY AND PHENOLIC AND FLAVONOID CONTENT OF Ocimum basilicum L. CALLUS CULTURES OBTAINED BY DIFFERENT PLANT GROWTH REGULATORS - Topdemir, Aykut; Buran, Abayhan (Univ Life Sciences Lublin, 2023)
In this study, binary combinations of five plant growth regulators (PGR) were used for the cultivation of Ocimum basilicum L. calluses. Antioxidant properties, phenolic and flavonoid contents of O. basilicum L. calluses were determined by keeping the concentrations and solvents of PGR constant.The total phenolic content of ethanol extracts of O. basilicum L. calluses was between 1.044 +/- 0.188 and 0.417 +/- 0.049 mg of GAE/g; total phenolic content of methanol extracts was between 2.547 +/- 0.110 and 0.701 +/- 0.095 mg of GAE/g. The total flavonoid content of ethanol extracts was between 2.058 +/- 0.122 and 0.446 +/- 0.063 mg of quercetin/g, whereas the total flavonoid content of methanol extracts was between 3.010 +/- 0.336 and 0.341 +/- 0.041 mg of quercetin/g. The antioxidant content of ethanol extracts was between 2.826 +/- 0.141 and 5.736 +/- 0.201 mmol/g of Trolox equivalent antioxidant capacity (TEAC) and the antioxidant content of methanol extracts was between 4.186 +/- 0.394 and 1.050 +/- 0.211 mmol/g of TEAC.
Keywords: Ocimum basilicum L; callus; phenolic substance; flavonoid; antioxidanta